Multi-objective learning control for robotic manipulator - Khin Kyu Kyu Win. (2008)
A multi-objective learning control problem is formulated and solved. The primary objective is to satisfy the robotic manipulator’s desired end-effector motion and several secondary objectives are specified for the desired orientation and for obstacles avoidance.